COMPARATIVE STUDY OF MENTAL WELL-BEING IN TEENAGERS WITH WORKING MOTHERS IN THE PRIVATE SECTOR AND HOMEMAKERS ATTENDING PUBLIC AND PRIVATE SCHOOLS IN LAHORE, PAKISTAN - REHMAN , AU; JAFFAR , F; REHMAN , SU; ELAHI , A; AKBAR , R; AFZAL , A; MUJAHID , MUF; DEVI , J; MEHMOOD , R; BILAL , M; IBRAGIM , Y; SHAIKH , R; et al. (Biological and Clinical Sciences Research Journal, 2023)
Mental health plays a vital role in our ability to think, feel, interact, work, and enjoy life individually and collectively. A person's mental health is affected by several things at any moment, some of which are social, psychological, and biological. Children of working mothers may have different degrees of anxiety, depression, and social problems. Adolescents' mental health has been the subject of countless global studies. Still, less is known about the differences in adolescent mental health between children whose mothers work and those whose mothers do not work outside the home. This research aimed to compare students' mental health in public and private schools in Lahore based on their mothers' employment and its correlation with other socio-demographic characteristics. The research was cross-sectional and included 150 randomly chosen people from many different strata. The collected data were entered and analyzed using SPSS version 26.0. The majority of students we checked attended private schools. The study findings revealed no significant association between the mental health status of adolescents and their mothers' working status, especially in the private sector. However, a noteworthy correlation was observed between mental health status and gender. The average score for mental health assessment was not satisfactory. In conclusion, this research found no statistically significant difference in adolescents' mental health across groups depending on their mothers' employment level. The results indicated that a mother's employment or lack thereof had little impact on her children's psychological health. However, when comparing the mental health of male and female students, there was a clear gender gap. Adolescents' mental health was not significantly affected by factors like their mothers' education, the sort of household they were born into, their birth order, or their parents' monthly income. To learn more about this issue, researchers should investigate how teenagers see their parents' parenting styles in the future.